2004
DOI: 10.1021/jf035290s
|View full text |Cite
|
Sign up to set email alerts
|

Human Fecal Metabolism of Soyasaponin I

Abstract: The metabolism of soyasaponin I (3-O-[alpha-L-rhamnopyranosyl-beta-D-galactopyranosyl-beta-Dglucuronopyranosyl]olean-12-ene-3beta,22beta,24-triol) by human fecal microorganisms was investigated. Fresh feces were collected from 15 healthy women and incubated anaerobically with 10 mmol soyasaponin I/ g feces at 37 degrees C for 48 h. The disappearance of soyasaponin I in this in vitro fermentation system displayed apparent first-order rate loss kinetics. Two distinct soyasaponin I degradation phenotypes were obs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
55
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(65 citation statements)
references
References 28 publications
10
55
0
Order By: Relevance
“…The parental constituent soyasaponin I showed a peak at m/z 941 [M-H] − ion. Of these metabolites, M1 and M3 were soyasaponin III and soyasapogenol B, respectively, as previously reported (Hu et al, 2004 , which matched that of soyasapogenol B 3-β-D-glucuronide.…”
Section: Metabolism Of Soyasaponin Isupporting
confidence: 85%
See 1 more Smart Citation
“…The parental constituent soyasaponin I showed a peak at m/z 941 [M-H] − ion. Of these metabolites, M1 and M3 were soyasaponin III and soyasapogenol B, respectively, as previously reported (Hu et al, 2004 , which matched that of soyasapogenol B 3-β-D-glucuronide.…”
Section: Metabolism Of Soyasaponin Isupporting
confidence: 85%
“…The pharmacological effects of these soyasaponin, or triterpenoid glycoside, constituents of natural products may depend on their metabolism by intestinal bacteria (Kobashi and Akao, 1997;Kim, 2002). Hu et al (2004) reported that human fecal microflora potently hydrolyzed soyasaponin I via soyasaponin III to soyasapogenol B. However, they did not find other metabolite(s).…”
Section: Introductionmentioning
confidence: 98%
“…Soyasaponins vary in the composition of their sapogenol as well as the number, type, and point(s) of attachment of their sugar moieties to the sapogenol. Berhow, & Singletary, 2005Gurfinkel & Rao, 2003;Hu, Reddy, Hendrich, & Murphy, 2004a;Hu, Zheng, Hyde, Hendrich, & Murphy, 2004b) and one in vivo study (Koratkar & Rao, 1997) conducted to investigate the anti-mutagenic or anti-carcinogenic properties of soyasaponins. These studies have shown soyasaponins suppress the growth of cancer cells and the effect of soy saponins depend on the type of saponin, dose and cancer cell lines tested.…”
Section: Introductionmentioning
confidence: 99%
“…tract, and that they are metabolized by gut microflora into their aglycone soyasapogenol. To better understand this process, Hu et al (2004b) conducted a human fecal metabolism study which tracked the metabolism of the primary soyasaponin in heat treated soy foods, soyasaponin I (Murphy, Hu, Barua, & Hauck, 2008). The results show that soyasaponin I is rapidly metabolized within the first 24 hours by microflora into soyasaponin III.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation